Status of primary and secondary mental healthcare of people with severe mental illness: an epidemiological study from the UK PARTNERS2 programme. Issue 2 (15th February 2021) - Reilly, Siobhan; McCabe, Catherine; Marchevsky, Natalie; Green, Maria; Davies, Linda; Ives, Natalie; Plappert, Humera; Allard, Jon; Rawcliffe, Tim; Gibson, John; Clark, Michael; Pinfold, Vanessa; et al.
Abstract : Background: There is global interest in the reconfiguration of community mental health services, including primary care, to improve clinical and cost effectiveness. Aims: This study seeks to describe patterns of service use, continuity of care, health risks, physical healthcare monitoring and the balance between primary and secondary mental healthcare for people with severe mental illness in receipt of secondary mental healthcare in the UK. Method: We conducted an epidemiological medical records review in three UK sites. We identified 297 cases randomly selected from the three participating mental health services. Data were manually extracted from electronic patient medical records from both secondary and primary care, for a 2-year period (2012–2014). Continuous data were summarised by mean and s.d. or median and interquartile range (IQR). Categorical data were summarised as percentages. Results: The majority of care was from secondary care practitioners: of the 18 210 direct contacts recorded, 76% were from secondary care (median, 36.5; IQR, 14–68) and 24% were from primary care (median, 10; IQR, 5–20). There was evidence of poor longitudinal continuity: in primary care, 31% of people had poor longitudinal continuity (Modified Modified Continuity Index ≤0.5), and 43% had a single named care coordinator in secondary care services over the 2 years. Conclusions: The study indicates scope for improvement in supporting mental health service delivery in primary care. Greater knowledge of how care is organised presents an opportunity to ensure some rebalancing of the care that all people with severe mental illness receive, when they need it. A future publication will examine differences between the three sites that participated in this study.